The Communication Skills of Tour Guides in Handling Customers - ., I NENGAH SUARDHANA; ., Prof. Dr. Putu Kerti Nitiasih, MA; ., Prof. Dr.I Nyoman Adi Jaya Putra, MA (Jurnal Pendidikan Bahasa, 2013)
Suardhana Nengah I (2013),